Developing a School Finance System for K-12 Reform in Qatar - Guarino, Cassandra M. (RAND Corporation, 2009)
Reform-minded leaders of Qatar, who have embarked on a sweeping reform of their nation's education system, asked RAND to evaluate their education finance system and offer suggestions for improvements. The authors analyze the system's evolution and resource allocation patterns between 2004 and 2006 and develop analytic tools for performing the evaluation, including a framework that allows assessment of the system in light of six main objectives.